Differential cross sections for elastic and inelastic positronium–hydrogen-atom scattering - Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 2001)
We report results of differential cross sections for elastic scattering, target-elastic Ps excitations, and target-inelastic excitation of hydrogen in a five-state coupled-channel model allowing for [Formula Presented] and [Formula Presented] excitations using a recently proposed time-reversal-symmetric regularized electron-exchange model potential. The present model yields a singlet Ps-H S-wave resonance at 4.01 eV of width 0.15 eV and a P-wave resonance at 5.08 eV of width 0.004 eV. We also study the effect of the inclusion of the excited Ps and H states on the convergence of the coupled-channel scheme. © 2001 The American Physical Society.